ANALYSIS OF LOCATION QUOTIENT AND SHIFT SHARE IN RIAU PROVINCE - Ariyanto, Anto; Harmaidi, Desma; Khairunnas, Khairunnas; Yasid, Hamdan (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Sustainable economic growth is an absolute requirement for the economic development of a region, both on a regional and national scale. The government should develop sectors that are capable of providing a multiplier on other sectors. This is also very much needed by the Province of Riau. This study aims to identify and analyze the leading sectors that have competitive competitiveness and to determine the priority of the base sector as information material and considerations especially for the Provincial Government of Riau in the development of economic development in the future. This study uses secondary data in the form of Riau Province sectoral GDP and Indonesia's sectoral GDP based on constant 2010 prices. The type of data collected is in the form of a time series from 2015 to 2021 obtained from the Central Bureau of Statistics of Riau Province and the Indonesian Central Bureau of Statistics. The data is then analyzed with a quantitative descriptive approach using the Location Quotient (LQ). Based on the LQ method, there are 3 leading sectors in Riau Province, namely Agriculture, Forestry and Fisheries, Mining and Quarrying and Processing Industry. The three sectors have an LQ above 1, which means that these sectors are the base sectors. The three PDRB sectors from 2015–2021 have continued to increase except for the mining and quarrying sector which has continued to decline every year but is still the basis sector for economic growth in Riau.